Quality of life in individuals with patellofemoral pain: A systematic review including meta-analysis. (September 2018) - Coburn, Sally L.; Barton, Christian J.; Filbay, Stephanie R.; Hart, Harvi F.; Rathleff, Michael S.; Crossley, Kay M.
Abstract: Objective: The aim of this systematic review is to describe QoL in individuals with PFP, and determine the impact of PFP interventions on QoL. Methods: Five databases were searched for studies reporting QoL in individuals with PFP, with mean age under 50 years. Data were pooled based on QoL tool (e.g. Knee Injury and Osteoarthritis Outcome Score [KOOS] QoL subscale, Short-Form 36 item health survey [SF-36]) using random-effects models, or through narrative synthesis where inadequate data were available. Results: Individuals with PFP, had worse KOOS-QOL scores (pooled mean: 47[95% CI: 34 to 61] and health-related QoL (pooled SF-36 PCS and MCS: 47[95% CI: 41 to 53] and 54[95% CI: 47 to 62], respectively) compared with pain-free controls and population norms. Physical interventions were associated with improvements in knee- and health-related QoL in individuals with PFP in repeated measures studies. However, the effect of physical interventions compared to a control treatment was conflicting. Conclusion: Individuals with PFP aged under 50 years, have markedly reduced knee- and health-related QoL compared to pain-free controls and population norms. Knee- and health-related QoL may improve following intervention, but it is unclear if these improvements are greater than that which occur in a control group. Highlights: People with patellofemoral pain have impaired quality of life. Quality of life is worse than the general population. Quality of life is worse than pain-free people. Physical therapy may improve quality of life.